TRANSLATION QUALITY OF EXPRESSIVE SPEECH ACT IN THE NOVEL ENTITLED BREAKING DOWN (AWAL YANG BARU) WRITTEN BY STEPHENIE MEYER - Hari Nugraha (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2019)
AbstractTranslation of speech acts is an interesting activity considering the process of understanding the message in it, must be related to the context (speech situation). Speech acts are one part of language that is defined as actions that contain utterances. This study was written with the aim of analyzing the speech acts used in the novel entitled